Effect of Aspirin Consumption during Pregnancy on Fetal and Placental Weights and Histomorphometric Changes of the Fetal Stomach in Rats - Maryam Heydarzadeh; Mahnaz Azarnia; Seyed Homayoon Sadraie; Gholamreza Kaka; Majid Naghdi (Journal of Advanced Biomedical Sciences, 2015)
Background & Objective: Due to the relevant use of aspirin to relieve pain and common symptoms of gastric ulcer and possible malicious effects on fetus, this study investigates the histomorphologic effects of aspirin on the stomach tissue in rat embryos.